Assessing Scrum Maturity and Organizational Performance in Agile Telecommunications Software Development Projects - Muhammad Awaluddin (Arthatama: Journal of Business Management and Accounting, 2023)
The rapid pace of digital transformation requires organizations, particularly in the telecommunications sector, to adopt agile methodologies to improve software development performance. This study aims to analyze the level of Scrum maturity within the Business Process Digitization Tribe using the Scrum Maturity Model (SMM). A quantitative, survey-based approach was employed involving 52 respondents consisting of product owners, scrum masters, developers, QA engineers, and UI/UX designers. Reliability and validity testing confirmed that all constructs met the required thresholds. Descriptive analysis revealed that Basic Scrum Management achieved the highest score, while Iteration & Performance Management obtained the lowest. Structural Equation Modeling (SEM) confirmed that Iteration & Performance Management is significantly influenced by Basic Scrum Management, Requirements Engineering, and Customer Relationship Management, with 58% of the variance explained. The findings indicate that the Business Process Digitization Tribe has reached Level 2 (Managed) of the SMM, meaning that fundamental Scrum practices are consistently implemented, but limitations remain in performance measurement and Customer Relationship Management. This study contributes to the agile maturity literature and provides managerial insights, particularly recommendations for improving backlog refinement, strengthening performance metrics, and fostering a more mature agile culture.